The regime of intellectual property rights in politics Commercial: the cases of NAFTA and TMEC (Business Vision, 2019)
The free trade policy that in recent decades has been promoted by the dominant international regime and its large corporations has been a factor that encourages the free movement of productive factors to locate their productive phases in different countries according to the competitive advantages they offer for the production of goods and services; increasing your profits and the accumulation of capital; creating a global production system characterized by the intertwining of global value chains that take advantage of commercial deregulation to carry out interregional trade and production without respecting the delimitation of the economic blocks created in the nineties; what constitutes an expression of the freedom of investment and trade that has allowed the growth of emerging economies such as China, Mexico, Brazil, India that have been recipients of foreign investment in this global productive system. In this historical and economic framework, it is important to highlight the importance of the intellectual property aspects that have become more important with the advance of the fourth technological revolution, since they have become a lever for the development of nations and it is for this reason that countries that are more advanced in trademarks, inventions and patents take special care to protect their innovations and create international regimes that constitute legal frameworks consistent with their objectives of capital accumulation; This is done both through international trade bodies, and through multi-bilateral or free trade agreements such as the T-MEC signed recein.
Keywords: intellectual property; protectionism; T-MEC; fourth industrial revolution